(untitled) - Greenway, A. Roger (New York, 2003)
Topics include: Introduction to Air Permitting; Assessing Compliance with Clean Air Requirements; Ambient-Air Quality Monitoring; Liabilities and Enforcement; State Permitting program; and State Environmental Agencies. CD-ROM included.
Keywords: Environmental engineering,Air; Pollution